Factors affecting the application of strategic management accounting techniques and performance in Vietnamese enterprises - Tran , Thi Phuong Lan; Duong , Hoang Ngoc Khue; Tran , Hong Van; Ha , Xuan Thach (Journal of Finance - Marketing Research, 2025)
Purpose – The objectives of the study are to determine factors affecting the applications of strategic management accounting (SMA) techniques and the operational performance of Vietnamese enterprises. Design/methodology/approach - Using a mixed research method (qualitative research combined with quantitative research), with survey data from 262 medium and large non-financial enterprises in Vietnam. Data analysis and processing were performed using Smart-PLS software. Findings - Research results show that the factors including the competitive level of the environment, unstable level of the environment, ownership structure, business strategy, market orientation, organizational structure, and information technology have a positive on the application of SMA techniques, to the performance of Vietnamese enterprises. Originality/value - The application of SMA techniques has a positive impact on performance in Vietnamese enterprises. From the findings, the management policies are proposed to promote the application of strategic management accounting to increase sustainable performance in Vietnamese enterprises in the current period.